PENERAPAN ALGORITMA LEVENSHTEIN DISTANCE UNTUK PENCARIAN PADA SISTEM INFORMASI PERPUSTAKAAN FAKULTAS KEDOKTERAN UNIVERSITAS PALANGKA RAYA - Widiatry Widiatry; Nova Noor Kamala Sari; Viktor Handrianus Pranatawijaya; Putu Bagus Adidyana Anugrah Putra (Jurnal Saintekom)
The library of Faculty of Medicine of University of Palangka Raya is one of the libraries that regulates its management conventionally, and has not utilized computer technology optimally. So that, the library needs to improve its performance over the time, perticularly in delivering information on books or in terms of circulation services of book borrowing and returning transactions.